Class council and learning evaluation: tools of democratic management in public school - Miranda, Nonato Assis de (2017)
This paper presents the results of a qualitative research conducted in a public school in São Paulo with the intention to investigate the Class Council and Participatory Series (CCSP) as a space for collective evaluation and democratic management. It was found that the CCSP is an enabling space and strengthening the collective work in which coordination is the role of reorganizing the pedagogical work, from the results obtained. The CCSP, in the school investigated, is perceived as an opportunity for reflection that helps in building more democratic evaluation practices, reflecting the moment of transition by which the assessment passes, oscillating between the qualifying practice and training practice.